IMPLEMENTATION X-RAY RADIATION SAFETY MANAGEMENT IN RADIOLOGY LABORATORY OF ‘AISYIYAH YOGYAKARTA UNIVERSITY - Asih Puji Utami (Jurnal Imejing Diagnostik (JImeD), 2019)
Background:D3 Radiology Study Program is part of the new study programs at the Faculty of Health Sciences ‘Aisyiyah Yogyakarta University, which has accepted new students since 2016. In the learning process in the laboratory role is very important to support the success of the applied curriculum. So that the radiation safety management system is required in managing the laboratory, because radiation safety management is important for laboratory users, namely lecturers, assistant lecturers, and students. The purpose of this study was to analyze the implementation of X-ray radiation safety management at the Radiology Laboratory ‘Aisyiyah Yogyakarta University.Methods: This study uses descriptive qualitative research with data collection methods conducted in-depth interviews and observations. The sampling technique used was total sampling to all radiation workers as many as 12 people. Data analysis is done by reducing data, creating categorization tables and making, open coding so conclusions can be made. While presenting data in the form of quotations.Results:The results show that in the Radiology laboratory Aisyiyah YogyakartaUniversity already has a radiation protection organizational structure component consisting of an installation employer, radiation protection officers and radiation workers (8 lecturers and 4 Lecturer assistants). Health monitoring of radiation workers has been carried out during the process of submitting x-ray equipment permits. Radiology Laboratory of University 'Aisyiyah has sufficient radiation protection equipment. As for quality assurance, equipment they have quite complete. Suitability tests for radiographic equipment have been conducted during the process of permitting equipment, during learning and training for all lecturers and teaching assistants in 2016 and 2018. Monitoring individual doses are carried out using TLD, pen dosimeter, digital dosimeter.Conclusion: Document retention has been carried out but has not been well organized. While the education and training documents are still kept by each radiation worker on his personal documents.